Percepatan Pemulihan Ekonomi Desa Melalui Pendampingan Pengembangan Produk dan Digitalisasi Produk UMKM - Adi Pratama, Rohmawan; Mutiara, Arbelia; Nuur A, Annisa; Akhdan, Asyraf; Yudha, Dodi (Jurnal Ilmiah Pangabdhi, 2025)
Pucangan Village is a village located in Kartasura District, Sukoharjo Regency, Central Java. This village is approximately 15 km from Sebelas Maret University. With a total population of 13,842 people, according to field observations, around 80% of residents who run MSMEs in Pucangan Village have not mastered digital technology; only about 20% of people understand digital technology. In addition, PKK community organizations in Pucangan Village have not been optimally involved in the recovery of the village's economic acceleration. Pucangan Village has many potential natural and human resources that can be utilized, one of which is MSME products in the form of emping melinjo, crackers, and furniture businesses. But in reality, this potential has not been optimally developed because it does not know how to carry out digital marketing with the potential that exists in Pucangan Village. We can help by utilizing the resources in Pucangan Village as a dedication to economic development, especially surrounding MSMEs. In this digitalization era, marketing optimization through digital marketing is very important in order to improve the economy more quickly and efficiently. This training is useful to understand the digital marketing market, which has the potential to increase economic development. The purpose of this activity is to empower rural communities with human resources that can guide the community to become more developed, develop natural resources to be used more efficiently, and produce products that have value in the community with digitalization so that people know more about the market with a wider scope for MSMEs, especially rural communities. Increasing production and marketing of products in Pucangan Village with the establishment of a partnership between Pucangan Village and Sebelas Maret University can create an economy that is more open to the digital world, especially understanding production and marketing that will increase MSME productivity.